COVERAGE OF 9TH MAY INCIDENT: A FRAMING ANALYSIS OF PAKISTANI NATIONAL LEADING DAILIES - Nouraiz Ijaz; Saima Waheed (Journal of Peace, Development and Communication, 2024)
Media plays an important role to built public perception. It is fourth pillar of state. Especially when we talk about print media, it’s a source of information to educate people. This study examines “Coverage of 9th May Incident: A Framing Analysis of Pakistani National Leading Dailies”. In this research, researcher will analyzed the role of Pakistani leading newspapers that how media framed 9th May incident in newspapers. Various national and international studies have been reviewed in this research. Framing theory has been applied in this study. Content analysis has been used. Researcher selected two English Pakistani leading Newspapers, named: Dawn and The Express Tribune and two Urdu Pakistani leading Newspapers, named: Jang and Nawa-i-Waqt. In this research purposive sampling techniques used to analyze the data.